Sources of problems in milk supply chain in Serbia and its consequences - Slobodan, Aćimović; Jovan, Zubović; Domazet, Ivana (Economics of Agriculture, 2010)
This paper is the result of research efforts aimed to identify key problems in the milk supply chain in Serbia. Authors intend to indicate major issues in the Serbian milk market during last three months of summer 2010. In the introductory part of the research authors briefly define supply chain – a network of upstream-downstream links and the values in each chain. That is followed by the structure of the "milk flow" in Serbia, with basic performances of the market and analysis of most important participants in the market. After that we have analyzed causes of problems in the milk supply chain in Serbia, with detailed analysis of key issues related to supply chain structure (participants). Finally, we summarize with the consequences of structural problems in Serbia and provide solutions for them.